INOVASI MAHASISWA KKN-TEMATIK UNIRA DALAM PEMBUATAN PRODUK OLAHAN LELE UNTUK MENDONGKRAK PEREKONOMIAN MASYARAKAT DUSUN SEMBON KULON - Lailatul Rofiah; Wafiyatu Maslahah; Ayu Fitri Widiyanti (Universitas Islam Raden Rahmat Malang, 2022)
The devotion of students kkn-t 2 Unira to rural communities is to improve skills and lower the unemployment rate in sembon kulon's village. In the village of sembon kulon there are some citizens growing catfish and just for sale. Kkn-t students unira innovate, making a variety of processed basis catfish into nugget and crackers. But developing the innovation is a common obstacle, such as a lack of family knowledge of the potential of the catfish. So, therefore, socializing activities for a sembon kulon hillbilly community about how to make a signature based on catfish. From the results of these activities, citizens are expected to boost the economy of catfish breeding, and the surrounding communities.